Effects of nozzle types and 2, 4-D formulations on spray deposition. Issue 12 (1st December 2016) - Contiero, Robinson L.; Biffe, Denis F.; Constantin, Jamil; de Oliveira, Rubem S.; Braz, Guilherme B. P.; Lucio, Felipe R.; Schleier, Jerome J.
ABSTRACT: The objective of this study was to evaluate the effects of nozzle types and 2, 4-D formulations on spray deposition on different targets. Two field experiments were carried out in a completely randomized design, and treatments were arranged in a factorial scheme. Species in experiment 1 were Sumatran fleabane ( Conyza sumatrensis ) and Brazil pusley ( Richardia brasiliensis ) and in experiment 2 were soybeans ( Glycine max ) and Benghal dayflower ( Commelina benghalensis ). For both experiments, the first factor corresponded to spray nozzles with different settings (AD 110.015 – 61 and 105 L ha −1 ; AD 015-D – 75 and 146 L ha −1 ; XR 110.0202 – 200 L ha −1 ; and ADIA-D 110.02 – 208 L ha −1 ) and the second factor consisted of two formulations of 2, 4-D (amine and choline). The formulation of 2, 4-D choline has contained Colex-D™ Technology. Similar or higher spray deposition was observed on the leaves and artificial targets when using 2, 4-D choline as compared to the 2, 4-D amine formulation, and these differences in deposition were more evident for nozzles applying lower spray volumes. Deposition was more affected by nozzle type when amine formulation was used, compared to choline formulation.